Healthcare: Connecting technology and experts - Limmeren, Regine van (Technical Centre for Agricultural and Rural Cooperation, 2009)
A device that connects a mobile phone to a microscope lets rural lab workers in Uganda send photos of microscopic samples for expert analysis and diagnosis.